Pheromone communication in social insects : (Westview Press, 1998)
Characteristically, social insects rely heavily on behavioral mechanisms and associated pheromonal chemistry to maintain their sociality and to successfully function as a colony unit. Bringing together for the first time prominent researchers in social insect pheromone communication, including nestmate recognition, this book looks at ants, wasps, bees, and termites, highlighting areas of convergence and divergence among these groups, and identifying areas that need further investigation. Presenting broad synthetic overviews as well as species-specific studies, the volume will be useful to natural scientists, ecologists, and those interested in pest management, as well as to anyone interested in the fascinating chemically mediated behavioral interactions of social insects.